Elucidating the Regulon of a Fur-like Protein in Mycobacterium avium subsp. paratuberculosis (MAP) - Shoyama, Fernanda Miyagaki; Janetanakit, Taveesak; Bannantine, John P.; Barletta, Raul G.; Sreevatsan, Srinand (Frontiers in Microbiology, 2020)
Intracellular iron concentration is tightly regulated to maintain cell viability. Iron plays important roles in electron transport, nucleic acid synthesis, and oxidative stress. A Mycobacterium avium subsp. paratuberculosis (MAP)- specific genomic island carries a putative metal transport operon that includes MAP3773c, which encodes a Fur-like protein. Although well characterized as a global regulator of iron homeostasis in multiple bacteria, the function of Fur (ferric uptake regulator) in MAP is unknown as this organism also carries, IdeR (iron-dependent regulator), a native iron regulatory protein specific to mycobacteria. Computational analysis using PRODORIC identified 23 different pathways involved in respiration, metabolism, and virulence that were likely regulated by MAP3773c. Thus, chromatin immunoprecipitation followed by high-throughput sequencing (ChIP-seq) was performed to confirm the putative regulon of MAP3773c (Fur-like protein) in MAP. ChIP-Seq revealed enriched binding to 58 regions by Fur under iron-replete and deplete conditions, located mostly within open reading frames (ORF). Three ChIP peaks were identified in genes that are directly related to iron regulation: MAP3638c (hemophore-like protein), MAP3736c (Fur box) and MAP3776c (ABC transporter). Fur box consensus sequence was identified, and binding specificity and dependence on Mn2+ availability was confirmed by a chemiluminescent electrophoresis mobility shift assay (EMSA). The results confirmed that MAP3773c is a Fur ortholog that recognizes a 19-bp DNA sequence motif (Fur box) and it is involved in metal homeostasis. This work provides a regulatory network of MAP Fur binding sites during iron-replete and -deplete conditions, highlighting unique properties of Fur regulon in MAP.